Social incubation: Strategic benefits for social enterprise - Nascimento, Leandro da Silva; Fernandes, Bernardo Soares; Salazar, Viviane Santos (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This paper aimed to identify what are the strategic benefits that the social incubation process offers for social enterprise. We conducted a case study with a Brazilian social incubator. Social enterprises that participated in the social incubation program were the analysis units. Among the eight strategic benefits found, three of them have never been previously indicated in the studied literature, therefore being a novelty herein highlighted to improve social enterprise's commercial and social missions. By understanding these benefits, social entrepreneurs can make better decisions about joining social incubation. Besides, managers of social incubators can understand the limitations inherent to the social incubation herein stressed, and, from this, improve the programs. Hence, this paper advances knowledge in the social entrepreneurship field.